2014
DOI: 10.4244/eijv10i1a10
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised study of the paclitaxel-coated balloon catheter in bifurcated coronary lesions (BABILON trial): 24-month clinical and angiographic results

Abstract: pDEB bifurcation pretreatment with BMS implantation in MB showed greater LLL (ns) and increased incidence of MACE compared to everolimus DES. Both strategies showed similar results in the SB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…Following screening for replicates, 405 remained; and after screening abstracts for relevance, a further 371 studies were removed. Finally, full text of the remaining 34 studies were screened, of which 17 randomised controlled trials (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) fulfilled the inclusion criteria and were qualitatively and quantitatively analysed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following screening for replicates, 405 remained; and after screening abstracts for relevance, a further 371 studies were removed. Finally, full text of the remaining 34 studies were screened, of which 17 randomised controlled trials (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) fulfilled the inclusion criteria and were qualitatively and quantitatively analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, some studies were susceptible to industry bias owing to author involvement in relevant device companies such as B. Braun, Boston Scientific Medtronic and Eurocor GmbH (18,21,22,28,29,31,33). Similarly, conflicts of interest may have arisen due to these companies funding studies which investigated their own products (18,21,26,28,30,31,33,34).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PEB to treat the entire bifurcation lesion was examined by the BABILON Trial and the PEPCAD V Bifurcation Study [15,16]. In the PEB arm of the former study, both MV and SB were pre-treated by PEB, followed by BMS implantation to the MV.…”
mentioning
confidence: 99%
“…Therefore, DEB without stent treatment mostly focuses on high-risk restenotic lesions, such as small vessels, bifurcations, or ISR [4]. Several clinical trials have confirmed the safety of paclitaxel-coated balloon in patients with de novo lesions in small coronary arteries or in bifurcation lesions [12,13,23,24,25,26,27,28]. However, information on DEB treatment of non-small coronary artery lesions is limited.…”
Section: Discussionmentioning
confidence: 99%